Modification of the Association of B-Type Natriuretic Peptides With Mortality and Hospitalization Outcomes by Sex - David Bobrowski, MD; Husam Abdel-Qadir, MD, PhD; Candace D. McNaughton, MD, PhD, MPH; Anna Chu, MHSc; Xuesong Wang, MSc; Peter C. Austin, PhD; Barbara S. Doumouras, MD; Karem Abdul-Samad, BSc; Peter A. Kavsak, PhD; Michael E. Farkouh, MD, MSc; James L. Januzzi, MD; Heather J. Ross, MHSc, MD; et al. (JACC: Advances)
Background: The effects of sex on the prognostic implications of natriuretic peptide (NP) elevation have not been fully elucidated in the population. Objectives: The purpose of this study was to examine if sex modifies associations of NPs with mortality and hospitalization. Methods: In a population-based retrospective cohort study, we identified all patients (aged ≥40 years) undergoing NP testing in Ontario, Canada (2015-2020). We examined for the presence of sex-by-NP interactions for 1-year outcomes and conducted sex-specific analyses for continuously increasing NP concentrations. Results: We studied 91,017 individuals with B-type natriuretic peptide (BNP) tests (median 75 years; 48.0% females) and 81,578 individuals with N-terminal pro-BNP (NT-proBNP) tests (74 years; 48.6% females). Adjusted 1-year risks of all-cause mortality at any given NP concentration were higher in males than females. For example, 1-year mortality at a BNP of 400 ng/L was 16.8% in females and 21.6% in males. At an NT-proBNP of 900 ng/L, 1-year mortality was 14.2% in females and 18.5% in males. However, there were also significant sex interactions with BNP (P = 0.002) and NT-proBNP (P = 0.03) for mortality outcomes. When we examined cardiovascular hospitalizations, there was also a significant sex-by-NP interaction. For BNP, the risk of cardiovascular hospitalization was higher in males at lower concentrations but was higher in females at higher concentrations (P-interaction = 0.005). For NT-proBNP, the risk of cardiovascular hospitalization was higher in males at lower NP concentrations, but the gap narrowed at higher NP levels (P interaction = 0.03). Conclusions: Sex modifies the association between NP concentrations and all-cause mortality or cardiovascular hospitalizations. Prognostically, interpretation of NP levels should consider effect modification by sex.